Studi Eksperimental Karakteristik Tekanan Kapiler Pada Material Pad Hasil Aktivasi Bambu Betung Tanpa Holding Time - Sihombing, Reinhard Aditya Noversan; Wijaksana, Hendra; Astawa, Ketut (Teknik Desain Mekanika, 2022)
Abstract In the development of this era, it is widely known that global warming that occurs on the earth is increasing and therefore in an effort to get a comfortable level in the room, a cooling system that is more energy efficient and environmentally friendly is needed. One alternative cooling system is the system direct evaporative cooling. In direct evaporative cooling systems, material pads are used as a heat transfer medium which is useful for increasing the contact area between air and water. The basic material for the pad material used is local bamboo betung from Bali. This study aims to analyze the effect of variations in activation temperature on the characteristics of capillary pressure on bamboo betung activated charcoal whose temperatures are varied starting from 500oC, 600oC, 700oC, and 800oC then activated with a temperature of 600 ° C without holding time. . This test includes several tests such as SEM test, contact angle test, and capillarity test. The results of all tests indicate that the MKA 800 specimen has a very good suitability as a pad material in asystem direct evaporative cooling with a pore radius of 29.16 m, a contact angle of 36.60and the highest capillary pressure of 39890.26 N/m2. Keywords: Direct Evaporative Cooling, bamboo betung, material, carbonization, activation and capillarity.